Comment: We Study the Present to Understand the Past. - Vecoli, Rudolph J. (Journal of American Ethnic History)
Presents several views on the trend in the study of the social history of immigration in the United States elaborated in the 1998 American Historical Association Meeting in Seattle, Washington. Approaches in the study of the challenges faced by immigration history in the US; Importance of cultural anthropology in defining the field of immigration history; Discussion on ethnicity.